HISTORYJA BARZO CUDNA O STWORZENIU NIEBA I ZIEMIE KRZYSZTOFA PUSSMANA – STRATEGIE TŁUMACZENIA - STELMACH, WOJCIECH (Slavia Occidentalis, 2020)
The goal of this article is primarily to present the translation strategies adopted by Krzysztof Pussman in the course of working on Historyja barzo cudna o stworzeniu nieba i ziemie. The 16th-century apocrypha has slipped into oblivion – it was last discussed by Stanisław Dobrzycki in 1911. Research suggests that the translator-cum-compiler in fact followed the trends developed in his times. A compilation of the results of analyses and elaborations on the language and the way of translating other Old Polish apocrypha confirms this statement. The deliberations presented in this article, ordered by theme (the author divided the material into issues related to syntax, vocabulary, inflexion, rhetoric and style) provide an outline of broad research perspectives related to Historyja barzo cudna… as an independent historic work and in a comparative perspective (with other apocrypha texts of the time and old Polish canonical texts).